1999
DOI: 10.1038/sj.bjc.6690121
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of a major role for the PTEN tumour-suppressor gene in breast carcinomas

Abstract: Breast carcinoma represents the most common malignancy of women in Western countries. Despite its prevalence, the molecular mechanisms of breast cancer formation and progression are still poorly understood. Molecular studies suggest that tumoursuppressor genes involved in hereditary tumour formation may also be altered in their sporadic counterparts (Fearon, 1997). Five per cent of all patients with breast carcinomas report a family history and the majority of these familial cases have been associated with ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 24 publications
(23 reference statements)
1
33
1
1
Order By: Relevance
“…utah.edu/genesnps; refs. 9,19). No associations with breast or prostate cancer risk have been reported; however, these studies have not been comprehensive with respect to surveying common genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…utah.edu/genesnps; refs. 9,19). No associations with breast or prostate cancer risk have been reported; however, these studies have not been comprehensive with respect to surveying common genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33] There is an increased predilection for breast cancer caused by germline mutations of PTEN (lifetime risk 450% in patients with Cowden's disease) however, mutations are rare in sporadic breast cancer. [34][35][36] Previous studies have demonstrated association between loss of PTEN expression or reduced PTEN expression in breast cancer with stage, lymph node status, disease-related death, and loss of ER. [20][21][22][23][24]37 Two of these studies included small number of unselected cases.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic syndromes associated with a predisposition to thyroid cancer include Cowden disease (Liaw et al, 1997); ataxia telangiectasia (Swift et al, 1987); inherited multiple endocrine neoplasia type II (Schimke, 1984); familial adenomatous polyposis (FAP) and hereditary non-polyposis colorectal cancer (HNPCC) (Houlston and Stratton, 1995). However, few of these are considered to be an important cause of breast cancer (Warren et al, 1992;Fitzgerald et al, 1997;Freihoff et al, 1999;Inskip et al, 1999).…”
Section: Discussionmentioning
confidence: 99%